The influences on Calvin"s hermeneutics and the development of his method - Myung, Jun Ahn (Hervormde teologiese studies, 1999)
The article deals with Chrysostom and the humanists Valla, Budi and Erasmus who influenced Calvin's hermeneutics. Calvin appreciated Chrysostom's rejection of the allegorical interpretation and his emphasison the 'simple sense of the text'. The article aims at showing how Chrysostom and the humanists afected Calvin's hermeneutics of interpreting the 'intention of the author of Scripture' (mens scriptoris) and seeing the 'true meaning' of the text as, simply and briefly, (brevitas etfacilitas) as possible.